FINANCIAL MECHANISM OF MANAGEMENT OF THE PUBLIC DEBT OF THE REPUBLIC OF KAZAKHSTAN - G. A. Mataibaeva,; S. B. Makysh,; O.V. Kopylova , (Academic Journal of Physical and Chemical Sciences, 2019)
The financial mechanism is an active element in the system of governance, economics and finance in society. In any state for the implementation of financial policy, its successful implementation is used, as an element of management and regulator of economic relations, a financial mechanism. It is a combination of ways of organizing financial relations used by society in order to ensure favorable conditions for economic and social development. The financial mechanism includes the types, forms and methods of organization of financial relations, methods for their quantitative determination. The financial mechanism is considered in action, it is active and includes complex elements, has a subsystem. The complex system of economic mechanism, its links, levers, elements is in constant change, interaction in accordance with the tasks put forward and solved at a certain stage in the development of society, its production relations, or part of these relations associated with the development of a particular sphere, branch of the national economy.